MIDDLE EAST VECTOR IN THE POLICY OF THE LEADING WORLD POWERS - T. Chikaidze; U. Tedeeva (Гуманитарные и юридические исследования, 2021)
The authors aim to consider the factors that led to the geopolitical transformation of the Middle East region into a turning-point post-war decade marked by the shift of «centers of power» and the emergence of new actors of world politics. Advocating for the formation of new parameters of relations, the ruling circles of Great Britain with the strengthening of positions in the Middle East, intended to compensate for the loss of India, but such aspirations were torpedoed by the rise of anti-British nationalism, the anti-imperialist course of the USSR, and the anti-colonial doctrine of the United States. In addition to the ideological confrontation of the superpowers in the post-war period, the struggle for geostrategic superiority and access to the region's oil resources was wondrous. Along with the growing influence in the financial and economic sphere of the Middle East region, hegemonic aspirations were traced in US policy. Given the nature of American interests in the Middle East and the speciicity of the domestic political component of the United States, which plays a fundamental role in shaping foreign policy, United States policy was neither consistent nor correct. A large-scale approach to solving political problems, sometimes leading to crises, put the ruling circles of the United States in front of the need to re-evaluate and modify foreign policy. So the US efforts in the post-war decades were aimed at neutralizing and further limiting Soviet influence in the Middle East region, and Washington also adhered to tactics of containing conflicts and confrontation at the regional level. The fundamental aspect for the Soviet side, of the activation in the Middle East direction has been the desire to achieve security guarantees for its southern borders. In addition, the position aimed at diversifying ties favored the advancement of the foreign policy interests of the USSR in the status of a superpower. An analysis of archival materials and research literature allows us to conclude that the foreign policy priorities and principles of the leading world powers had a wide resonance in the region. Therefore, the formation of political coalitions and the rivalry of the States of the Middle East was partly supported from outside.